1999
DOI: 10.1177/001872679905200202
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Psychological Empowerment Among Service Workers: The Effect of Support-Based Relationships

Abstract: Data from 292 service workers in 21 private clubs show that supportive peer and customer relationships are predictive of higher levels of employee experienced empowerment. Both organizational and employee-customer relationships accounted for significant variation in the dimensions of empowerment: meaningfulness, influence, and self-efficacy. Peer helping and supportive customer relationships were the two most influential predictors of all three empowerment dimensions. Implications for future research and for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 36 publications
7
91
0
14
Order By: Relevance
“…For instance, Coates et al (1997) identified efficiency gains, lower turnover, better employee-employer relations, potential for a better bottom line, access to information, participation in decision making, discretion over work processes, enhanced employability, support for family responsibilities, affirmation of an independent voice for workers, and input into a range of workplace issues as benefits of high organizational performance for organizations, employees, and unions. In a competitive environment in which organizations must be faster, learner, provide better service, be more efficient, and ultimately more profitable, an empowered, and proactive workforce is thought to be essential (Corsun & Enz, 1999). In other words, the manager-employee relationship be altered in service industries to reflect the impact of the relationship between service workers and customers.…”
Section: Management's Response To Problems Of Industrial Relations Inmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Coates et al (1997) identified efficiency gains, lower turnover, better employee-employer relations, potential for a better bottom line, access to information, participation in decision making, discretion over work processes, enhanced employability, support for family responsibilities, affirmation of an independent voice for workers, and input into a range of workplace issues as benefits of high organizational performance for organizations, employees, and unions. In a competitive environment in which organizations must be faster, learner, provide better service, be more efficient, and ultimately more profitable, an empowered, and proactive workforce is thought to be essential (Corsun & Enz, 1999). In other words, the manager-employee relationship be altered in service industries to reflect the impact of the relationship between service workers and customers.…”
Section: Management's Response To Problems Of Industrial Relations Inmentioning
confidence: 99%
“…Moreover, an empowered workforce is better able to provide high quality customer service. Thus, a source of competitive advantage capable of differentiating an organization from others is its people and how they work (Coates et al, 1997;Corsun & Enz, 1999;Posthuma, 2010;ACAS, 2013;Colvin, 2013).…”
Section: Management's Response To Problems Of Industrial Relations Inmentioning
confidence: 99%
“…Plusieurs études rapportent des cas d'échec des pratiques d'habilitation du supérieur et montrent que leurs avantages potentiels sont souvent limités faute de mettre en place les conditions adéquates (Ahearne, Mathieu et Rapp, 2005 ;Ford et Fottler, 1995 ;Randolph, 2000). Certains chercheurs ont ainsi suggéré que le soutien social jouerait un rôle prépondérant dans la réussite de l'habilitation (Corsun et Enz, 1999 ;Hackman, 1987 ;Kirkman et Rosen, 1999 ;Logan et Ganster, 2007 ;Mathieu, Gilson et Ruddy, 2006 ;Parker et Price, 1994 ;Peccei et Rosenthal, 2001 ;Spreitzer, 1996). Ainsi le second objectif de cette recherche est de tester le rôle modérateur du soutien managérial perçu sur la relation entre l'habilitation du supérieur et la performance adaptative.…”
Section: Résumé De L'articleunclassified
“…Certaines études montrent que les avantages potentiels de l'habilitation ou d'un processus de délégation peuvent être réduits faute de mettre en place des conditions favorables, en particulier en l'absence d'un soutien suffisant accordé aux employés (Corsun et Enz, 1999 ;Hackman, 1987 ;Hackman et Oldham, 1980 ;Kirkman et Rosen, 1999, Logan et Ganster, 2007Mathieu, Gilson et Ruddy, 2006 ;Parker et Price, 1994 ;Peccei et Rosenthal, 2001 ;Spreitzer, 1996). L'habilitation peut avoir un côté sombre aussi bien pour les employés que pour leurs supérieurs (Spreitzer, 2007).…”
Section: Le Soutien Managérial Perçuunclassified
“…For years, there have been different attempts to discuss various issues associated with empowering employees (Menon, 1999;Corsun & Enz, 1999). Zimmerman (1992Zimmerman ( , 1995, for instance, discussed various aspects of psychological empowerment and concluded that the development of a universal and global measure of psychological empowerment may not necessarily be a feasible or appropriate objective.…”
Section: Introductionmentioning
confidence: 99%